1977
DOI: 10.1111/j.1432-1033.1977.tb11699.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin S Travis: a Sickling Hemoglobin with Two Amino Acid Substitutions [β6(A3)Glutamic Acid → Valine and β 142(H20) Alanine → Valine]

Abstract: Hb S Travis is a previously undescribed sickling hemoglobin with two amino acid substitutions in the β chain: β6 Glu → Val and β142 Ala→ Val. The β6 Glu→Val mutation imparts to Hb S Travis the characteristic properties of sickling hemoglobin, namely its association with erythrocyte sickling, the insolubility of the hemoglobin in the reduced form, and a minimum gelling concentration value identical to Hb S. Unlike Hb S, Hb S Travis exhibits an increased oxygen affinity and a decreased affinity for 2,3‐bisphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…HbS-Travis is the third non-S sickling Hb variant to be described after HbC-Harlem and HbC-Ziguinchor. HbS-Travis was first discovered in five members of a Black family in Travis, USA, as reported by Moo-Penn et al, 22 in 1977. All of the five studied family members were heterozygotes.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…HbS-Travis is the third non-S sickling Hb variant to be described after HbC-Harlem and HbC-Ziguinchor. HbS-Travis was first discovered in five members of a Black family in Travis, USA, as reported by Moo-Penn et al, 22 in 1977. All of the five studied family members were heterozygotes.…”
Section: Introductionmentioning
confidence: 77%
“…Genetic analysis revealed that HbS-Travis has two amino acid substitutions in the β-globin chain that include βGlu6Val and βAla142Val, 22 which most probably arose as a result of genetic crossing-over between HbS gene (βGlu6Val) on chromosome 11 and another chromosome carrying the βAla142Val mutation. 22 Electrophoretically, HbS-Travis moves to a position between HbS and HbF at alkaline pH, but at acidic pH it moves between HbA and HbS. 22 Nonetheless, HbS-Travis and HbA can be separated by anion exchange chromatography as it elutes immediately before HbA.…”
Section: Introductionmentioning
confidence: 99%
“…However, if ESI-MS can easily discriminate between the masses of b A -and b S -globin chains (−30 Da), this will never clearly confirm that the mutation lies on residue b6. Conversely, in a globin chain already carrying the Hb S mutation, the presence of a second substitution may modify the electrophoretic and chromatographic properties of the variant (Table 1) (20)(21)(22)(23)(24)(25)(26)(27). Such a variant, which has a clinical risk directly linked to the Hb S substitution, will not be recognized as an "atypical form" of Hb S. This is the case of Hb S-Clichy, in which the second mutation leads to the loss of a positive charge that masks the loss of the negative charge of the Hb S substitution, resulting in a variant with a charge close to that of Hb A.…”
Section: Discussionmentioning
confidence: 99%
“…L'électrophorèse de l'Hb de contrôle effectuée à l'âge de 12 ans a montré un profil électrophorétique proche de celui d'un porteur du trait drépanocytaire ( Quelques cas très rares de SDM, décrits dans la litté-rature, sont dus à des doubles mutants Hb comportant la mutation ␤ 6 val et une autre mutation en cis dans la chaîne ␤-globine. Plusieurs ont été décrits dans la littérature : HbS-Antilles [23], HbS-Oman [24], HbS-Cameroon [9], HbSProvidence [16], HbS-Travis [17], HbS-Clichy [18], HbS-South End [19] HbC-Ziguinchor [20], HbC-Harlem [8], Hb-Jamaïca Plain [21]. Ces doubles mutants ont un comportement élec-trophorétique à pH alcalin similaire à celui de l'HbS ou de l'HbC, plus rarement à celui de l'HbA (HbS-Providence, HbSSouth End).…”
Section: Dans Le Second Casunclassified
“…Cela est le cas pour les HbS-Travis [17], HbC-Ziguinchor [20] et HbC-Harlem [8], mais aussi l'HbS-Cameroon [9] et l'HbS-Providence [16]. L'HbS-Travis, associée à la mutation ␤ S en trans est responsable d'une précipitation de l'Hb au sein des globules rouges avec une relative instabilité et une auto oxydation augmentée.…”
Section: Dans Le Premier Cas éTudiéunclassified